Proarrhythmic effect of automatic threshold testing algorithm in dual chamber devices - Larsen, Timothy R.; Sargent, Donna; Moyes, Meredith; Huizar, Jose F.; Tan, Alex Y.; Ellenbogen, Kenneth A.; Kaszala, Karoly (Journal of cardiovascular electrophysiology, 2020)
Background Operation of auto‐threshold testing (ATT) algorithm in current dual chamber cardiac devices require temporary shortening of atrio‐ventricular (AV) delay to accurately measure evoked potential (capture) after a pacing pulse. Near simultaneous AV pacing causes atrial pressure elevation and may be associated with atrial arrhythmias. Objective We evaluated the prevalence of atrial arrhythmias induced by ATT in Abbott devices. Methods Device clinic records were reviewed at a single center for patients with dual chamber Abbott pacemaker/ICD. ATT‐induced atrial fibrillation (AF) cases were defined as new appropriate mode switch episodes while the ATT was operating. The auto‐capture test trends were defined as unstable if there were deviations >1 V in capture threshold trend events that did not correlate with routine in‐office testing. Results One hundred and seventy patients were programmed in dual chamber pacing mode. The ventricular ATT was active in 118 patients and of these 78 had true mode switch episodes. Six patients developed AF during ventricular ATT. Three patients had most recorded atrial arrhythmias in close association with ATT (63%, 66%, 100% vs 2%,9%, 33% in other patients with known prior AF). An unstable auto‐capture trend curve was seen in 33 patients (6 showing ATT‐induced AF) versus 85 patients with stable auto‐capture curve and no ATT‐induced AF (P = .0001, the χ2 test). Conclusion Ventricular auto‐capture algorithm use is associated with induction of AF in dual chamber Abbott devices with a prevalence of over 5%. AF occur more frequently (18%) in patients with erratic ventricular ATT trend results.